Improving the efficiency of image guided brachytherapy in cervical cancer - Otter, Sophie; Franklin, Adrian; Ajaz, Mazhar; Stewart, Alexandra (Journal of Contemporary Brachytherapy, 2016)
Brachytherapy is an essential component of the treatment of locally advanced cervical cancers. It enables the dose to the tumor to be boosted whilst allowing relative sparing of the normal tissues. Traditionally, cervical brachytherapy was prescribed to point A but since the GEC-ESTRO guidelines were published in 2005, there has been a move towards prescribing the dose to a 3D volume. Image guided brachytherapy has been shown to reduce local recurrence, and improve survival and is optimally predicated on magnetic resonance imaging. Radiological studies, patient workflow, operative parameters, and intensive therapy planning can represent a challenge to clinical resources. This article explores the ways, in which 3D conformal brachytherapy can be implemented and draws findings from recent literature and a well-developed hospital practice in order to suggest ways to improve the efficiency and efficacy of a brachytherapy service. Finally, we discuss relatively underexploited translational research opportunities.